Program management complexity : a competency model - Levin, Ginger; Ward, J. LeRoy (Boca Raton, FL : Auerbach Publications, 2011)
'Although complexity is a phenomenon that confounds and challenges program managers across industry sectors, there is little information available that identifies the set of competencies managers need to complete their program successfully and deliver the benefits desired by stakeholders. Program Management Complexity: A Competency Model fills this void. Written by two of the first professionals to obtain the (PgMP{u00A6}#x02bc;) certification from the Project Management Institute (PMI), this book begins with a literature review of program and project management complexity. Next, it presents a competency model, based on the authors seven decades of collective experience in the field, which follows the framework of PMI's model for project managers. Useful for corporate and government organizations, universities, executives, PMO directors and human resources professionals who need to determine program management training needs, this unique model is divided into performance competencies and personal competencies. The performance competencies are organized according to the six domains of program management, while the eight personal competencies are based on research plus a survey of PgMPs{u00A6}#x02bc; worldwide. After presenting the model, along with detailed plans and guidelines for its implementation in a real-world setting, the book presents three questionnaires designed to help organizations, existing program managers, and aspiring program managers assess their own development plans. Supplying you with the insight to recognize the elements of complexity during the defining and initiating stages, this book includes detailed guidelines to help you recruit, train, and develop program managers capable of delivering stated program benefits, services, and results'--
'Preface As two of the first individuals to attain the Project Management Institute's (PMI) Program Management Professional (PgMPʼ) credential, we recognized in our studying of the PMI Program Management Standard (2006) and other key literature in the field, that little attention had been paid to the topic of complexity in program management. While both the first and second editions of the PMI's The Standard for Program Management (PMI, 2006, 2008b) note the importance of managing the projects in a program in a coordinated way to ensure that program benefits are achieved, neither edition addresses the complexity inherent in the interdependencies of such projects. Moreover, the topic of the complexity of programs has not been specifically addressed in the rather meager selection of books and other publications on program management now available in the marketplace. Additionally, there is little, if any, information available today identifying a set of competencies a program manager needs to possess to successfully complete his or her program and deliver the benefits desired by stakeholders. This book fills this void. We offer a competency model based on more than 70 years of collective experience in the field, as well as drawing from other authoritative sources, that can help existing program managers assess where they can enhance their own skills, while also providing prospective program managers information so they, and others, x Preface'--
Book is accompanied by one CD/diskettes entitle' Program management complexity
Includes bibliographical references and index.
Keywords: Project management; Project managers